Does Position Affect Reduction? Comparison of the Effects of Three Different Positions on Reduction in Intertrochanteric Femur Fracture Nailing - Nezir Okumuş; Ahmet Nadir Aydemir (Medicina, 2025)
Background and Objectives: Our study aimed to retrospectively examine the routine radiographs on the first postoperative day of osteosynthesis applications performed in the supine position with the help of a traction table, in the lateral decubitus position, and in the supine position in patients with intertrochanteric fractures of the femur who had a proximal femoral nail applied. It also aimed to compare them in terms of radiology. This study investigated the effects of three different patient positions on fracture reduction, a topic rarely encountered in the literature. Materials and Methods: Patients who underwent proximal femoral nailing in three different positions—the supine, traction table, and lateral decubitus positions—due to femoral intertrochanteric fractures in two different centers were analyzed. A total of 157 patients with complete early radiographs were included in this study to evaluate the quality of postoperative reduction and fixation. Results: There was a significant difference between the traction table-assisted supine position group (mean: 25.31 mm) and both the lateral decubitus position (mean: 31.91 mm) and supine position (mean: 31.79 mm) groups in terms of the TAD (p = 0.000). Regarding the collodiaphyseal angle, the traction table-assisted supine position (mean: 130.720°) and lateral decubitus position (mean: 130.290°) groups showed significantly higher values than the supine position group (mean: 124.190°) (p = 0.000). The average lengths of the lag and compression screws were lower in the lateral decubitus position group compared with the other groups (p = 0.000). Patients in the supine position group had smaller nail diameters and lengths (p = 0.000). When examining the Cleveland–Bosworth lag screw placements, the most frequent position was center–center, including 22 patients (31%) in the traction table-assisted supine position group, 15 patients (30.6%) in the lateral decubitus position group, and 9 patients (24.3%) in the supine position group, though the difference was not statistically significant (p = 0.203). Among the reduction criteria we investigated, the TAD on the traction table was statistically significantly closer to the targeted measurement, with an average of 25.31 mm, compared with the other two positions (p = 0.000). The collodiaphyseal angle was significantly within the target range in the traction table-assisted supine group, averaging 130.720°, compared with the supine position (p = 0.000). In the traction table group, according to the modified Baumgaertner classification, 59.2% achieved a good reduction; according to the Ikuta classification, subtype N accounted for 69.4%; and according to the Cleveland–Bosworth classification, a center–center placement was present in 31% of patients. Conclusions: All three types of operation can be preferred according to the habits of the surgeon operating and the variables during the operation (the fracture type, history of orthopedic surgery, and the material components of the application phase). Accompanied by these data, we recommend the traction table operation as a priority and the lateral decubitus position operation as a second preference in compliance with the technical requirements.